Pendampingan Komunitas Belajar di Platform Merdeka Mengajar Sekolah - Zuni Tyas Eka Rifayanti; Noviardani Kartika Prameswari; Wachid, Lita Aditya Khoirun Nisa (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2025)
The transition from the 2013 curriculum to the independent curriculum has an impact on learning, especially for educators in Indonesia. This condition indicates that educators are the main element in implementing the curriculum in schools. Lack of training, seminars, and workshops has resulted in confusion for educators in implementing the independent curriculum. Therefore, Lecturers have duties and mandates that are outlined in the Tridharma activities. One of the Tridharma activities is Community Service which was carried out at SDN Gumuksari 1, Kalisat District, Jember regarding the formation of a learning community on the PMM platform as a form of implementing Direction and sharing good practices with several other educators through the Merdeka Mengajar Platform Learning Community. The purpose of this PKM activity is a form of social responsibility carried out by lecturers to make a positive contribution to the community. This activity is not only beneficial for the recipients, but also provides valuable experience for the devotees. The method used in PKM is a mentoring method involving seven educators at the school. The results of this PKM are that the participants showed high enthusiasm to start being active in the PMM Study Group. Most educators expressed their desire to immediately form study groups according to their respective fields of expertise and interests. Therefore, it can be concluded that the learning group activities to support the implementation of the Independent Curriculum more effectively. With the mentoring method implemented, educators feel more confident in using technology and can work together with colleagues, which will have a positive impact on the quality of learning in each school.